Regulating energy gap in Ir-based ionic complexes to generate near-infrared emissions: Application in solid-state light-emitting electrochemical cells - Lin, Yan-Ding; Hsiao, Pei-Wan; Chen, Wun-Yu; Wu, Sih-Yu; Zhang, Wei-Min; Lu, Chin-Wei; Su, Hai-Ching (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •Investigate a series of cationic iridium complexes with extremely small energy gaps, with 2,2'-bibenzo[d]thiazole fixed as N^N ligand moiety mainly controlling the LUMO energy level, changing a series of C^N ligands.•All targeted complexes exhibited deep red/NIR phosphorescence, and these combined devices provided emission peaks at 690–730 nm and were applied as components in LECs, exhibiting a maximum EQE of 1.78% in electroluminescence devices.•Using a host-guest emission system with the iridium complex YIr as the host and complex TBBI as the guest, the highest EQE of LECs could be further enhanced to more than 2.34%, which is the highest value reported for NIR LECs. Solid-state light-emitting electrochemical cells (LECs) exhibit high potential for commercial electronics owing to their simple solution-processable device architectures, low-voltage operation, and compatibility with inert metal electrodes. However, the low device efficiency of most deep-red and near-infrared (NIR) LECs hinders their application (external quantum efficiency (EQE) < 1.00%). In this study, we demonstrate a simple method to tune the energy gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of iridium-based ionic transition metal complexes (iTMCs) to generate NIR emissions. We investigate a series of cationic iridium complexes with small energy gaps, with 2,2′-bibenzo[d]thiazole fixed as N^N ligand moiety mainly controlling the LUMO energy level, changing a series of C^N ligands. All complexes exhibited deep red/NIR phosphorescence, and these combined devices provided emission peaks at 690–730 nm and were applied as components in LECs, exhibiting a maximum EQE of 1.78% in electroluminescence devices. Using a host–guest emission system with the iridium complex YIr as the host and complex TBBI as the guest, the highest EQE of LECs could be further enhanced to>2.34%, which is the highest value reported for NIR LECs.